Apolipoprotein E and Alzheimer's disease - Benjamin R. Troutwine; Laylan Hamid; Colton R. Lysaker; Taylor A. Strope; Heather M. Wilkins (Elsevier, 2022)
Genetic variation in apolipoprotein E (APOE) influences Alzheimer's disease (AD) risk. APOE ε4 alleles are the strongest genetic risk factor for late onset sporadic AD. The AD risk is dose dependent, as those carrying one APOE ε4 allele have a 2-3-fold increased risk, while those carrying two ε4 alleles have a 10-15-fold increased risk. Individuals carrying APOE ε2 alleles have lower AD risk and those carrying APOE ε3 alleles have neutral risk. APOE is a lipoprotein which functions in lipid transport, metabolism, and inflammatory modulation. Isoform specific effects of APOE within the brain include alterations to Aβ, tau, neuroinflammation, and metabolism. Here we review the association of APOE with AD, the APOE isoform specific effects within brain and periphery, and potential therapeutics.